2019
DOI: 10.1007/s42764-019-00005-7
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between signaling pathways and DNA damage response

Abstract: Living organisms have developed a complex signaling system to sense diverse growth signals and co-ordinate intracellular bioprocesses, so that they survive in various conditions. Since organisms are often exposed to environmental and genomic threats which cause DNA damages, DNA damage response (DDR) and repair systems are important for maintenance of genome stability and integrity. A line of evidences has demonstrated that there is tight crosstalk between growth signaling pathways and DDR systems. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Here, we provide a simple overview of these mechanisms. For a comprehensive description of the complex pathways involved, we refer the reader to extensive review articles previously published [ 11 , 12 , 13 ]. Interstrand crosslinks (ICLs), generated either by natural or synthetic compounds, are mostly resolved via the Fanconi Anemia (FA) pathway [ 14 ].…”
Section: The Dna Damage Response Is Activated Upon Sensing Of Dna mentioning
confidence: 99%
“…Here, we provide a simple overview of these mechanisms. For a comprehensive description of the complex pathways involved, we refer the reader to extensive review articles previously published [ 11 , 12 , 13 ]. Interstrand crosslinks (ICLs), generated either by natural or synthetic compounds, are mostly resolved via the Fanconi Anemia (FA) pathway [ 14 ].…”
Section: The Dna Damage Response Is Activated Upon Sensing Of Dna mentioning
confidence: 99%
“…Occasionally, the depletion of a specific nutrient, such as choline, can play an important role in inducing apoptosis in infected cells [ 50 ]. Arginine depletion may lead to the inhibition of the mTOR pathway, thus indirectly activating DNA damage pathways, such as ATM/ATR, which may also explain the cell cycle arrest and apoptosis in cells with a high microorganism load [ 51 ]. Furthermore, mycoplasma deaminases hydrolyse L-arginine into L-citrulline and NH 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, several studies have suggested that PM2.5 possibly decreases the DNA repair capacity [66,69]. Furthermore, recent investigations have found that DDR might be affected by crosstalk with a number of signaling pathways, such as PI3K/AKT, NF-kB and, so on [83]. As mentioned above, PM2.5-induced ROS production has been documented to activate these signaling pathways, further implicating its role in the interruption of DDR.…”
Section: Oxidative Stress-impaired Dnamentioning
confidence: 95%
“…In fact, living organisms are always exposed to a variety of risk factors, both exogenous and endogenous, that might be harmful to genome stability and integrity, possibly leading to various types of DNA damage. Luckily, a complicated signaling network including DNA repair and cell cycle checkpoint pathways, also referred to as the DNA damage response (DDR), is activated in response to DNA damage in order to function as an "anti-cancer barrier" [83]. If compromised DNA is inappropriately restored by DDR, the genomic mutations and other irreversible damage will occur, subsequently leading to severe consequences such as malignant progression.…”
Section: Oxidative Stress-impaired Dnamentioning
confidence: 99%